The European Society of Radiotherapy and Oncology (ESTRO) European Higher Education Area levels 7 and 8 postgraduate benchmarking document for Radiation TherapisTs (RTTs) - Leech, Michelle; Coffey, Mary (My University, 2018)
This guideline details the European Higher Education Area Levels 7 and 8 Postgraduate benchmarking document for Radiation TherapisTs (RTTs). The purpose of this benchmarking document is to assist higher education institutes in the development of radiation therapy-specific curricula for RTTs engaging in postgraduate education, with a view to working at an advanced level in radiation therapy departments. The document specifies the knowledge, skills and competences that are required to work in specific areas of RTT practice, at levels 7 and 8. These include: advanced delineation and volume determination, advanced treatment planning, advanced imaging, quality and risk management, management and service development, patient care and support, brachytherapy and research.
PUBLISHED
Keywords: Education; Postgraduate; Advanced practice; Benchmarking; Cancer; Radiation Therapy